2016
DOI: 10.1007/978-3-319-17722-9_7
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Adoption and Use by Australian Capital City Local Governments

Abstract: This chapter explores social media adoption and use by Australian capital city local governments. Despite digital communication with the community being an integral part of modern local government functions, the types of digital communication being used are not commonly monitored or analyzed in the Australian context. This chapter provides an investigation of the types of social media being employed by local governments and a sentiment analysis of Twitter accounts from a sample of local governments in Sydney. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…A similar pattern was found in other European countries such as Belgium and Italy, where Twitter and Instagram have been adopted by a minority of municipalities. These results are in line with previous literature, showing that adoption of Facebook is growing rapidly with an increasing number of municipalities using it in their communication (Mossberger et al, 2013;Bonsón et al, 2016;Gruzd and Roy, 2016;Williamson and Ruming, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…A similar pattern was found in other European countries such as Belgium and Italy, where Twitter and Instagram have been adopted by a minority of municipalities. These results are in line with previous literature, showing that adoption of Facebook is growing rapidly with an increasing number of municipalities using it in their communication (Mossberger et al, 2013;Bonsón et al, 2016;Gruzd and Roy, 2016;Williamson and Ruming, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…However, this study discovered that community engagement on social media is crucial for strengthening both strong and weak ties on social media, which can predict community resilience. Previous studies have also suggested that community engagement on social media is a fundamental part of the community resilience mechanism and plays a vital role in activating the potential of social capital on social media for better community resilience [9], [46].…”
Section: Discussionmentioning
confidence: 99%
“…This is mainly due to three reasons: no information provided by the authors (13 studies), use of an automated approach (4 studies), or use of a manual approach (6 studies) [539,540,159,541,542,543] to perform a form of social opinion mining. Regarding the former, the majority of them [544,545,546,547,548,549,550,551] were not specifically focused on social opinion mining (this was secondary), in contrast to the others [552,553,554,555,556]. As for the automated approaches [557,558,559,560], some of them used cloud services, such as Microsoft Azure Text Analytics 59 or out-of-the-box functionality provided by existing tools/software libraries, such as the TextBlob 60 Python library.…”
Section: Othermentioning
confidence: 99%